2010
DOI: 10.4102/sajip.v36i1.442
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of a psychosocial stress and coping model in the police work context

Abstract: Orientation: Stress is a social reality which does not exist in isolation, but in many social situations, especially work-related environments. Police officers in particular suffer from highly negative stress related outcomes.Research purpose: The purpose of the study was to determine how Moos's hypothesised stress and coping model (1994) fitted a sample of police officers.Motivation for the study: The study was an attempt to understand police officers' unique needs and how the frequency and/or intensity of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 62 publications
0
22
0
4
Order By: Relevance
“…As a result, multiple role expectations for working women (Valk & Srinivasan, 2011) are evident. Both work and family are an indispensable part of their lives and to reconcile their roles in both spheres is challenging (Louw & Viviers, 2010), especially for those involved in the emotionally demanding and stressful profession of nursing. Irregular shift work, dealing with emergencies, incivility and work overload are integral challenges of the nursing profile.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, multiple role expectations for working women (Valk & Srinivasan, 2011) are evident. Both work and family are an indispensable part of their lives and to reconcile their roles in both spheres is challenging (Louw & Viviers, 2010), especially for those involved in the emotionally demanding and stressful profession of nursing. Irregular shift work, dealing with emergencies, incivility and work overload are integral challenges of the nursing profile.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of jobrelated stress and negative work-family interference, female police personnel who have access to adequate social support may not experience adverse effects of job stress that emanate from job demands compared with those who do not have such opportunities (Rivera-Torres, Araque-Padilla & Montero-Simó, 2013). Studies among police personnel suggest that negative interface between work and family demands increased job stress (Bazana & Dodd, 2013;Louw & Viviers, 2010). In a study involving 533 Polish citizens, Merecz and Andysz (2014) reported that negative interface of work and family demands compounded job stress and culminated in more incidence of occupational burnout.…”
mentioning
confidence: 99%
“…However, a number of factors have been found to mediate the relationship between longterm stress or adversity, and the individual's experience of a sense of well-being (Friborg, Hjemdal, Rosenvinge, & Martinussen, 2003;Ryff & Singer, 2003). For example, factors such as an individual's perception, appraisal and appropriate use of personal and social resources during stressful life events (Clark et al, 2007;Koolhaas, de Boer, & Buwalda, 2006;Louw & Viviers, 2010) have received substantial research attention.…”
Section: Please Scroll Down For Articlementioning
confidence: 98%